The Effect of Per Capita Income, Human Resource Quality, Environmental Quality, and Unemployment on Happiness in Indonesia - Hari Pradana, Ananda Rizky; Fitanto, Bahtiar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Indonesia has recorded a relatively stagnant happiness index year after year and tends to lag behind other Southeast Asian countries, despite improvements in various development parameters such as per capita income, Human Development Index (HDI), Environmental Quality Index (EQI), and Open Unemployment Rate (OUR). This study analyzes the effect of per capita income, human resource quality, environmental quality, and unemployment on happiness in Indonesia using panel data and the Two-Stage Least Squares (2SLS) estimation method with the Fixed Effects model. The results show that human resource quality and environmental quality positively affect per capita income, while unemployment has a negative effect. Furthermore, per capita income has a positive and significant effect on happiness. This study emphasizes the importance of policies focusing on improving access to education, healthcare quality, environmental quality, and job creation to enhance the well-being and happiness of the population sustainably.